Wettability device for electronic solder alloys using the sessile drop method - Souza, Héricles Ruiliman Oliveira de (2025)
Fil: Souza, Héricles Ruiliman Oliveira de. Universidade Federal do Pará. Instituto de Tecnologia; Brasil.